ANALISIS FAKTOR YANG MEMPENGARUHI MINAT BERSEKOLAH ANAK DI TELUK MEKU LANGKAT, SUMATERA UTARA - isnaini; Nazliati; Nina Rahayu (Pusat Studi Gender dan Anak, 2022)
The realization of children as the nation's next-generation is one of the efforts to strengthen the nation's competitiveness in facing world challenges. However, how can children be able to face the world's challenges when children who are the nation's successors are still on the verge of neglect in the field of education. This research was conducted in Teluk Meku Langkat Village, North Sumatra. This study aims to analyze what factors influence children's interest in attending school in Teluk Meku Langkat Village, North Sumatra. Using descriptive qualitative and in-depth interviews and distributing questionnaires given to parents, children, and classroom teachers, the researchers found that three factors influence children's interest in school, namely the interests of children, parents, and teachers.